Iodized Salt Processing Technology through Solar Thermal Salt House in Sanolo Village - Agrippina Wiraningtyas; Ahmad Sandi; Ruslan Ruslan (Institute for Research and Community Services, 2019)
The Community Partnership Program reported in this paper aimed to produce iodized salt using the innovative Solar termal Salt House in increasing the production and productivity of salt pond land with low costs and sustainability. The method used was the salt crystallization technique produced by small salts and then washed with brine to remove impurities to obtain white, shiny, salt crystals. The crystals obtained were then dried in the Solar Thermal Salt House to protect them from pollution and dust particles. The dried salt crystals were sorted using a filter to get a uniform crystal size before they were iodized and packaged for sales. The iodized salt was sold at a price of 1,000.00 IDR for 250 grams. The results showed that producing iodized salt through the Solar Thermal Salt House was able to help the participants to increase the production and productivity of their pond land. The use of geothermal plastic as a crystallization table was shown to be able to increase the quantity and quality of salt products in Sanolo Village, Bolo District, Bima Regency. It was also found that odized salt production mulitiplied farmers' income by up to 400%, as well as changes in their behavior in the application of science and technology to produce salt.